The Coordination Chemistry of the Phosphanylborane (C6H5)2PBH2·N(CH3)3 towards Copper(I) Salts. Issue 26 (19th May 2020) - Elsayed Moussa, Mehdi; Braese, Jens; Marquardt, Christian; Seidl, Michael; Scheer, Manfred
Abstract : The reactions of the phosphinoborane Ph2 PBH2 · NMe3 with Cu (I) halides [CuCl, CuBr, CuI] and [Cu(CH3 CN)4 BF4 ], respectively, were studied. Depending on the ratio of the reactants used, the former reaction allowed for the synthesis of eight neutral coordination compounds with the general formula [Cu n X n (Ph2 PBH2 · NMe3 ) m ] (X = Cl, Br, I; n = 1, 2, 4, 5; m = 2, 4) (4–11 ). The latter reaction, however, led to the formation of the homoleptic complex [Cu(Ph2 PBH2 · NMe3 )3 ][BF4 ] (13 ). The structures of the products 4 –11 and 13 were compared to related complexes possessing the well‐known Ph3 P ligand. All compounds were characterized by single crystal X‐ray structure analysis, multinuclear NMR spectroscopy, IR spectroscopy and mass spectrometry. Abstract : Phosphine‐copper(I) complexes have been attracting increasing attention as earth abundance based candidates for a variety of applications. Herein, we present the synthesis of eight neutral and one cationic complexes from the reaction of the phosphanylborane Ph2 PBH2 · NMe3 with Cu (I) halides and [Cu(CH3 CN)4 ][BF4 ], respectively. The obtained products belong to a rare class of phosphine–copper(I) coordination compounds.